Effects of clay-mineral type and content on the hydraulic conductivity of bentonite–sand mixtures made of Kunigel bentonite from Japan. (1st February 2019) - Kohno, Masanori; Nara, Yoshitaka; Kato, Masaji; Nishimura, Tsuyoshi
ABSTRACT: Clay-mineral type and content, bulk mineralogical composition and alteration of bentonite are very important factors for the ultra-long-term stabilization of barriers and backfills in radioactive waste disposal. This study investigates the effects of clay-mineral type and content on the swelling characteristics and permeability of bentonite–sand mixtures with clay minerals using one-dimensional swelling-pressure and constant-pressure permeability tests. The hydraulic conductivity of bentonite–sand–clay mineral mixtures increased with increasing content of non-swelling alteration products of montmorillonite. Furthermore, hydraulic conductivity was comparable to that determined with the Kozeny–Carman equation for a specific surface area, suggesting that hydraulic conductivity may be estimated based on the abundance of expected alteration products of montmorillonite. This study provides a basis for evaluation of the hydraulic conductivity of bentonite–sand mixtures with known quantities of expected alteration products of montmorillonite.